Estrategias de enseñanza de Lectoescritura en la educación infantil (2023)
This research seeks to demonstrate strategies about children's literacy based on various contexts about it, where traditional strategies must be left aside, since it is a problem because early-age students tend to discover the world in a very active way. Given this case, it is intended to imply that the strategies involve processes to find a better way of learning, since to achieve the purposes used in reading and writing, a good understanding of its characteristics is needed in order to achieve good progress. In addition, 12 articles were observed that lead to strategies that disrupt the traditional. With this mode, the strategies are where students manage to adapt skills and critical thinking, based on the interest that the infant achieves to have assertiveness in what they want to learn.